Islamic welfare system dealing with the poor in rural area - Zakiyah Zakiyah (IAIN Salatiga, 2011)
This paper try to review the practice of Islamic welfare system (such as zaka,waqf, shadaqa, infaq, hibah and qurban) dealing with poor people in rural area.Then, this study looks at four main issues, namely how the structure of thecommitee, the management of such system, fund rising strategy, and peopleaccessibility to this welfare system. In order to deal with this, it is used someframeworks namely; firstly, the welfare strategy as proposed by Spicker (1995)including economic production, redistribution, and solidarity. Secondly, the conceptof welfare offered by Azmi (1991), Midgley (1997), and Zastrow (2004).This research took place in North and South Wonorejo, a village located in Magelangdistrict, Central Java. Finding of this research shows that this scheme has operatedconventionaly and has not contributed much on enhancing people welfare.There is no formal institution that organizes all element of such scheme. As thesocial welfare institution, this system ideally offers program, benefits and servicesthat help people meets those social, economic, educational and health needs.However, there is no specific program for the poor people offered by the committeeof the Islamic welfare scheme. Studi ini berusaha mengkaji praktik system kesejahteraan dalam Islam (sepertizakat, wakaf, shadaqah, infak, hibah dan qurban) dalam hubungannya denganmasyarakat miskin di wilayah pedesaan. Kajian melihat empat persoalan utama,yakni bagaimana struktur panitia, pengelolaan sistem kesejahteraan, strategipengumpulan dana, dan akses masyarakat terhadap sistem tersebut. Untukmenjawab persoalan ini, kajian mempergunakan kerangka kerja antara lain strategikesejahteraan sebagaimana diusulkan Spicker (1995) termasuk produksi,redsitribusi, dan solidaritas ekonomi, dan konsep kesejahteraan sebagaimanadikemukakan Azmi (1991), Midgley (1997), dan Zastrow (2004). Kajian inidilakukan di Desa Wonorejo Utara dan Selatan, Magelang, Jawa Tengah. Kajianini menemukan antara lain: skema kesejahteraan masih dilakukan secarakonvensional dan tidak banyak berkontribusi terhadap kesejahteraan masyarakat.Tidak ada lembaga resmi yang mengorganisir semua unsur dalam skema tersebut.Sebagai lembaga kesejahteraan sosial, sistem ini idealnya menawarkan program,manfaat dan layanan yang menolong masyarakat dalam memenuhikebutuhan-kebutuhan ekonomi, sosial, pendidikan dan kesehatan. Namundemikian, tidak ada program khusus bagi masyarakat miskin yang ditawarkanoleh pengelola skema kesejahteraan Islam.